(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Prostatic disease is responsible for significant morbidity and mortality in men throughout the world. Prostate cancer and benign prostatic hyperplasia are the two major prostate diseases that increase with aging. Histopathological examination of prostatic lesions has been gold standard for the final diagnosis. Objective: This study was carried out for histopathological evaluation of prostatic lesion and its correlation with the clinical data. Materials and Methods: This study included all types of prostatic specimens received in department of Pathology, AMC MET Medical College, Ahmedabad from January 2018 to December 2018. Relevant clinical data was recorded. Results: The most common age group presenting with prostatic lesion was 60-69 years and the most common presenting clinical symptom was difficulty in micturation. The frequency of benign and malignant lesions was observed to be 91% and 9% respectively. Amongst the benign lesions all lesions were Benign Prostatic Hyperplasia (BPH) with or without associated pathological lesions. All the malignant lesions were adenocarcinoma of prostate and were graded according to Gleasons scoring system. Predominant malignant lesions (40%) revealed Gleasons score 9. Strong correlation of S.PSA level with prostatic adenocarcinoma was seen in our study Conclusion: Histopathological evaluation seems to be gold standard for diagnosis, prognosis and management of prostatic lesions. S.PSA level has strong correlation with the risk and outcome of prostatic cancer.